Novel Polycarbonates via Phosgenation of Unsaturated Diols - Al-Muaikel, Nayef S. (Journal of Research Updates in Polymer Science, 2016)
A new interesting class of linear unsaturated polycarbonates based on methyl- cyclohexanone and 4-tert. butyl- cyclohexanone moieties has been synthesized. An interfacial phosgenation technique carried out at ambient temperature was used for the synthesis of these polycarbonates. The resulting polycarbonates were characterized by elemental analyses, infrared spectroscopy, 1H nuclear magnetic resonance spectral analyses, viscometry, differential scanning calorimetry and thermogravimetric analysis measurements. All the polycarbonates were soluble in polar solvents like dimethylsulphoxide and sulphuric acid. The crystallinity of some selected polycarbonates was examined by X-ray analysis. In addition, the morphology of selected examples of the polycarbonates was examined by scanning electron microscopy.